Stage in oil palm tissue culture - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Khairu Aidilnishah, Rizan Jalil; Mohd Asyrak, Deraman; Rajan, Jose; Aziah, Mohd Yusoff (Penerbit UMP, 2009)
Cloning through vegetative propagation is an attractive alternative to obtain offspring which possess the genetic make-up of the parents. In oil palm due to its morphology, tissue culture is the only option for vegetative propagation. Clonal material results in uniform growth and yield performance thus increase in yield per unit hectare. The parent plant, known as ortet is normally selected from high performing individuals with t raits as . per Table 1. In the selection of clones for production their amenability to tissue culture and their pro lificness in shoot production are additional selection criteria.